Bicrystal and dispersion strengthened WC-Ni-based hard alloy and preparation method thereof

By adding CR3C2 and VC to the composite grain growth inhibitors to the WC-NI base hard alloy, a small plate-shaped WC grains that are irregular and appearance are formed. The problem of WC-NI-based hard alloys during the sintering process of WC grain growth driving and easy to evaporate NI, which significantly improves the strength, toughness, and wear resistance of the alloy, and meet the requirements of the nuclear main pump mechanical sealing components.

CN119372537AActive Publication Date: 2025-01-28CENT SOUTH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411446881.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-28
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

During the sintering process, traditional WC-Ni-based cemented carbide has a large driving force for WC grain growth and is easy to evaporate, resulting in small WC grains and uneven microstructure structure, making it difficult to meet the strength, toughness and resistance of mechanical sealed parts of the nuclear main pump. Abrasive requirements.

Method used

Using dual-crystal and scattered strong WC-Ni base hard alloys, by adding CR3C2 and VCs as composite grain growth inhibitors, the growth of WC grains is regulated to form a small and small-shaped WC grain with irregular appearances, and in the Ni -base adhesion forms nano -scattered phase to improve the abrasion and toughness of the alloy.

Benefits of technology

A significant improvement of the BC-Ni-based hard alloy's curved strength, Vita hardness, and fracture toughness. The curved strength of the alloy can reach 3945MPa, the maximum hardness of Vita can reach 2060kgf/mm2, PALMQVIST fracture toughness KIC can reach up to 10.81 up to 10.81 MPA · M1/2 meets the strict requirements of the mechanical seal component of the nuclear main pump.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372537A_ABST
    Figure CN119372537A_ABST
Patent Text Reader

Abstract

The invention discloses a bicrystal and dispersion-strengthened WC-Ni-based hard alloy and a preparation method of the bicrystal and dispersion-strengthened WC-Ni-based hard alloy. The alloy is composed of a hard phase component WC, bonding metal Ni and super-saturated composite grain growth inhibitors Cr3C2 and VC. A WC hard phase in the alloy is composed of irregular morphology grains with the average grain size smaller than 0.5 micrometer and fine plate-shaped grains distributed in a dispersed mode, the typical morphology feature of the fine plate-shaped WC grains on the polished section of the alloy is in a long strip shape, the average length of the fine plate-shaped WC grains is smaller than 2.2 micrometers, and the average width of the fine plate-shaped WC grains is smaller than 0.5 micrometer; a nano dispersed phase exists in a Ni-based binder solid solution matrix in the alloy. Unsaturated carbon type nano WC powder is adopted as a raw material, and the alloy is endowed with the characteristics of high hardness, high toughness and high strength through ultra-fine grain strengthening of a hard phase, strengthening of dispersed fine platy crystals and strengthening of a nano dispersed phase of a binding phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a twin-crystal and dispersion-strengthened WC-Ni-based hard alloy and a preparation method thereof, and belongs to the field of low-carbon clean energy and high-performance hard new materials. Background Art

[0002] Nuclear energy is an important component of low-carbon clean energy. The nuclear main pump is a key component to maintain the safe operation of the nuclear reactor. The key components of the nuclear main pump mechanical seal are made of WC-Ni based cemented carbide.

[0003] The Vickers hardness of Ni and Co is 784MPa and 1784MPa respectively, and the stacking fault energy, which is negatively correlated with the work hardening ability and crack growth resistance, is 125mJ / m 2 and 20mJ / m 2 . Therefore, compared with WC-Co cemented carbide, it is difficult to improve the mechanical properties of pure WC-Ni cemented carbide, such as hardness, strength, and toughness. Due to its obvious advantages in particle size and purity, carbonyl Ni powder is the best choice for the preparation of Ni-containing hard materials. However, due to its rough surface, it is difficult to be evenly dispersed during the preparation of wet grinding mixtures, which easily leads to the aggregation of bonding phases in the alloy microstructure.

[0004] Grain refinement is an important means to improve the strength, hardness and wear resistance of alloys. The liquid phase appearance temperature of WC-Ni ternary alloy is 40-70℃ higher than that of WC-Co ternary alloy, and the vapor pressure of Ni is significantly higher than that of Co under liquid phase sintering conditions. Therefore, during the sintering process, the driving force of WC grain growth in WC-Ni-based alloy is significantly increased, and Ni is more likely to evaporate, making it difficult to obtain WC-Ni-based alloys with fine WC grains and uniform microstructure. The bending strength of traditional pure WC-Ni cemented carbide is usually lower than 2300MPa; under the conditions of the same WC grain size and bonding metal content in the alloy, the Rockwell hardness (HRA) of WC-Ni-based cemented carbide is more than 0.5 lower than that of WC-Co alloy. Therefore, the comprehensive performance of WC-Ni ternary alloy is difficult to meet the stringent requirements of strength, toughness, wear resistance and performance stability of WC-Ni-based cemented carbide in extreme service conditions represented by nuclear main pump mechanical seals.

[0005] Chinese patent CN101205584A "A high-hardness, high-strength, low-cost non-magnetic hard alloy" discloses that the alloy composition is 80-90 parts of WC, 5-20 parts of Ni, 0.5-5 parts of chromium carbide, 0.1-0.5 parts of vanadium carbide, 0.1-0.5 parts of molybdenum carbide, and the WC grain size in the alloy is 1.8-2.4μm, which belongs to the medium-coarse alloy grain size range. The porosity of the alloy prepared by this patent is as high as A06 and B06. High porosity will cause abnormal failure of key components of the mechanical seal of the nuclear main pump, seriously affecting the safe operation of the equipment. Summary of the invention

[0006] An object of the present invention is to provide a twin-crystal and dispersion-strengthened WC-Ni based cemented carbide which can be used as a key component of a nuclear main pump mechanical seal.

[0007] In order to achieve the above object, the present invention is a twin crystal and dispersion strengthened WC-Ni based cemented carbide, which is composed of a hard phase component WC, a bonding metal Ni and a composite grain growth inhibitor; the composite grain growth inhibitor is Cr3C2 and VC; the mass fraction of the bonding metal Ni in the alloy is 6.0-13.0%; the mass ratio of the grain growth inhibitor Cr3C2 to Ni is 12.0-25.0%, the mass ratio of VC to Ni is 3.0-4.0%, and the total amount of the composite grain growth inhibitor added exceeds room temperature conditions. The WC hard phase in the WC-Ni based cemented carbide is composed of irregular grains with an average grain size of less than 0.5 μm and dispersed fine plate-like grains, and the typical morphological feature of the fine plate-like WC grains in the polished cross section of the alloy is long strips with an average length of less than 2.2 μm and an average width of less than 0.5 μm; the bonding phase is a Ni-based solid solution formed by the solid solution of alloy components W, Cr, V and C in the bonding metal Ni during the alloy sintering process, and a nano-dispersed phase exists in the Ni-based solid solution.

[0008] Preferably, the twinned and dispersion strengthened WC-Ni based cemented carbide of the present invention is composed of hard phase component WC, bonding metal Ni and supersaturated composite grain growth inhibitor.

[0009] Preferably, the total amount of the composite grain growth inhibitor added has significantly exceeded its solid solution amount in the bonding phase at room temperature.

[0010] Another object of the present invention is to provide a method for preparing twinned and dispersion strengthened WC-Ni based cemented carbide.

[0011] In order to achieve the above object, the raw materials of the present invention include: nano-scale unsaturated carbon WC powder with an average particle size of less than 120nm in specific surface area, carbonyl Ni powder with a Fisher particle size of less than 1.2μm, and Cr3C2 powder and VC powder with a Fisher particle size of less than 1.2μm; the total carbon content of the unsaturated carbon WC powder is less than 6.12%; the preparation process includes:

[0012] A. Batching and dry premixing: nanometer-scale unsaturated carbon WC powder having a total carbon content of less than 6.12% and an average particle size of specific surface area less than 120nm, carbonyl Ni powder having a Fisher particle size of less than 1.2μm, and Cr3C2 powder and VC powder having a Fisher particle size of less than 1.2μm are batched so that the mass fraction of Ni in the raw material powder is 6.0-13.0%, the mass ratio of Cr3C2 to Ni is 12.0-25.0%, and the mass ratio of VC to Ni is 3.0-4.0%; the prepared raw material powders are dry premixed for 1-2 hours in an Ar gas protective atmosphere to form a premix;

[0013] B. Wet grinding: Wet grinding the WC-Ni based cemented carbide grinding balls, premix and composite forming agent in a wet grinding medium for at least 60 hours, preferably 60 to 72 hours, wherein the mass ratio of cemented carbide grinding balls to premix is ​​4:1 to 6:1, and the amount of the composite forming agent added is 2.2 to 2.4% of the total mass fraction of the powder;

[0014] C. Drying and granulating the mixture: using spray drying granulation or vacuum drying and mechanical granulation technology to prepare the wet-milled mixture into a mixture with an average particle size of less than 150 μm;

[0015] D. Forming: Press the granulated mixture into shape according to the shape and size of the product;

[0016] E. Removal of forming agent and sintering: a. Remove the forming agent from the green compact; b. After the forming agent is removed, vacuum sintering is performed in a pressure sintering furnace. When the temperature of the sintering furnace rises to 1250-1300°C, high-purity argon is introduced to make the pressure in the sintering furnace reach 8-10 kPa, and the temperature is kept for 60-80 minutes; c. When the temperature in the sintering furnace rises to 1410-1430°C, the amount of high-purity argon loaded in the sintering furnace is increased to raise the pressure in the sintering furnace to 5-8 MPa. a; d. Maintain the pressure in the sintering furnace at 5-8MPa, continue to raise the temperature to 1430-1450℃, and keep it warm for 15-20 minutes; e. Continue to maintain the pressure in the sintering furnace at 5-8MPa, reduce the temperature to 1410-1430℃ at a rate of 10-20℃ / min, and keep it warm for 80-120 minutes; f. Reduce the furnace temperature to 1000-1100℃ within 5-10 minutes; g. Cool down with the furnace to a product outlet temperature of less than 70℃;

[0017] F. Low temperature tempering: The tempering temperature is 400-450℃, the tempering time is 5-8 hours, and it is carried out under a protective atmosphere.

[0018] The wet grinding in step B is carried out in a drum ball mill.

[0019] The average grain size of the WC hard phase in the WC-Ni based cemented carbide grinding ball in step B is less than 0.8 μm, and Ni is used as the single bonding metal.

[0020] The wet grinding medium in step B is a mixed solution of alcohol and hexane; wherein the volume proportion of hexane in the wet grinding medium mixed solution is 5-10%.

[0021] In step B, the composite forming agent is composed of polyethylene glycol, paraffin and stearic acid, wherein the mass proportions of polyethylene glycol, paraffin and stearic acid in the composite forming agent are 20-30%, 60-70% and 10-15% respectively, and the total amount of the three is 100%.

[0022] The protective atmosphere in step F is vacuum or high-purity argon or high-purity nitrogen inert gas.

[0023] The inventors have found through research that, under the conditions of multiple factors coupling, the alloy of the present invention will be accompanied by the following phenomena during the sintering process: W2C reacts with Ni to form carbides (η phase) containing W and Ni, and then the η phase is in situ decomposed into Ni and active WC; W atoms in the active sites of the original WC are preferentially dissolved in Ni; through the dynamic behavior of dissolution and precipitation of W atoms in Ni, active WC grains and WC grains with prominent lattice distortion effects grow anisotropically, resulting in the formation of plate-like WC grains; by regulating the amount of active WC obtained by in-situ decomposition of the η phase, the number of active sites in the original WC, the type of grain growth inhibitor and its addition amount, effective regulation of the self-consistent behavior of the dispersed distribution of plate-like WC grains and its grain refinement can be achieved. The multiple factors include: (1) the presence of W2C and its amount in the unsaturated carbon WC that does not reach the theoretical carbon content; (2) the WC nanosize effect; (3) the WC lattice distortion effect caused by long-term intensive wet grinding for more than 60 hours; and (4) the synergistic behavior of the alloy components W, Cr, and V dissolved in Ni during the liquid phase sintering process.

[0024] The present invention is based on basic data such as the extremely poor solubility of alloy grain growth inhibitors Cr and V atoms in Ni under high-temperature sintering conditions higher than the eutectic temperature of the alloy system and the solubility of Cr and V atoms in Ni under room temperature conditions, as well as the change in the solubility of alloy components in Ni under the coexistence of W, Cr and V. The addition amount of Cr3C2 and VC composite grain growth inhibitors matching the alloy preparation process is designed; the eutectic temperature of the alloy system and the sintering temperature required for full densification are significantly reduced through component regulation and pressure regulation sintering of the alloy system, thereby strengthening the inhibitory effect on WC grain growth in the alloy and significantly inhibiting the evaporation behavior of Ni during the sintering process; the formation of the third phase of the supersaturated Cr3C2 and VC composite grain growth inhibitors is inhibited through rapid cooling at the sintering temperature; The addition of high-content corrosion-resistant promoting component Cr3C2 with less toughness damage to the alloy strengthens the grain growth inhibition effect of the alloy and significantly improves the wear resistance of the alloy; by regulating the environment for the in-situ formation of WC plate-like grains, the three-dimensional scale of the plate-like grains is effectively refined and the crystal integrity is effectively guaranteed, which significantly improves the intrinsic strength and wear resistance of the plate-like WC grains; based on the comprehensive strengthening effect of the hardness anisotropy of the plate-like WC grains and their effective hindrance to crack propagation, the hardness and fracture toughness of the alloy are simultaneously improved, solving the contradiction of the inverted relationship between hardness and toughness in traditional alloys; through low-temperature tempering, the internal stress formed by rapid cooling is reduced, so that the in-situ precipitation and self-consistent recombination of supersaturated solid solution atoms in the Ni-based bonding phase form a nano-dispersed phase reinforcement, thereby improving the hardness of the bonding phase and the hardness of the alloy.

[0025] The present invention adopts alcohol and hexane mixed wet grinding medium and polyethylene glycol, paraffin and stearic acid composite forming agent, which is helpful to achieve efficient dissolution of the forming agent, improve wet grinding crushing and wet grinding dispersion efficiency, and effectively solve the problem of difficult forming of nano powder.

[0026] The present invention realizes high crystalline integrity intrinsic strengthening through fine grain strengthening of WC hard phase in the alloy, plate-like crystal dispersion strengthening and self-consistent orderly growth, and realizes high strength of the alloy through nano-dispersed phase strengthening in the nickel-based bonding phase, and simultaneously improves the hardness and toughness of the alloy. The bending strength of the alloy can reach up to 3945MPa, and the Vickers hardness HV30 can reach up to 2060kgf / mm 2 , Palmqvist fracture toughness K IC The maximum value can reach 10.81MPa·m 1 / 2 , which can better meet the stringent requirements of the mechanical seal on the nuclear main pump for the strength, hardness, abrasion resistance, fracture toughness and performance stability of WC-Ni based cemented carbide material parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1This is a scanning electron microscope photograph of the microstructure of the WC-10.0Ni-1.2Cr3C2-0.4VC alloy in Example 1.

[0028] Figure 2 This is a metallographic photograph of the microstructural defects of the WC-10.0Ni-1.2Cr3C2-0.4VC alloy prepared in Example 1 without dry premixing, with the mixed material directly wet-milled for 50 hours, and without low-temperature tempering.

[0029] Figure 3 This is a scanning electron microscope photograph of the microstructure of the WC-6.0Ni-0.72Cr3C2-0.24VC alloy prepared in Comparative Example 2 using saturated carbon WC powder raw material with a total carbon content of 6.14%.

[0030] Figure 4 This is a scanning electron microscope photograph of the presence of Cr3C2 third phase in the microstructure of the WC-13.0Ni-3.25Cr3C2-0.39VC alloy prepared in Example 3 without rapid cooling and directly cooled from the sintering temperature.

[0031] Figure 5 This is a metallographic photograph of large cracks in the WC-13.0Ni-3.25Cr3C2-0.39VC alloy prepared in Example 5 using a single alcohol medium and a single polyethylene glycol forming agent accounting for 2.2% of the total mass of the mixture. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the embodiments and drawings.

[0033] Example 1

[0034] The experimental raw materials are as follows: specific surface area is 3.99g / cm 3 , unsaturated carbon WC powder with a specific surface area average particle size of 96nm and a total carbon content of 6.08%, carbonyl Ni powder with a Fisher particle size of 1.1μm, Cr3C2 powder with a Fisher particle size of 0.8μm, and VC powder with a Fisher particle size of 1.0μm. The preparation process is as follows:

[0035] A. Batching and dry premixing: The above raw material powders are used for batching so that the mass fraction of Ni in the raw material powder is 10%, the mass ratio of Cr3C2 to Ni is 12%, and the mass ratio of VC to Ni is 4%; the prepared raw material powders are poured into a dry mixing device, filled with Ar gas, and dry premixed for 1.5 hours in an Ar gas protective atmosphere to form a premix;

[0036] B. Wet grinding: using a drum ball mill and WC-8Ni-based cemented carbide grinding balls with an average grain size of 0.7 μm, the mass ratio of grinding balls to premix is ​​4:1, the grinding balls, the premix obtained in step A, a composite forming agent consisting of polyethylene glycol, paraffin and stearic acid accounting for 2.3% of the total mass of the mixture, and a mixed wet grinding medium of alcohol and hexane are added into a ball mill barrel, and the wet grinding time is 72 hours; wherein the mass proportions of polyethylene glycol, paraffin and stearic acid in the composite forming agent are 20%, 70% and 10% respectively, and the volume proportion of hexane in the wet grinding medium mixed solution is 5%;

[0037] C. Drying and granulating the mixture: using spray drying granulation to prepare the wet-milled mixture into a mixture with an average particle size of less than 150 μm;

[0038] D. Forming: According to the shape and size of the product, the granulated mixture is pressed into shape by molding process;

[0039] E. Removal and sintering of forming agent: The removal and sintering of forming agent are carried out in a 6MPa pressure sintering furnace, and the forming agent is removed according to the conventional forming agent removal process; after the removal of the forming agent, vacuum sintering is carried out in the furnace. When the temperature of the sintering furnace rises to 1250°C, high-purity argon is introduced to make the pressure in the sintering furnace reach 9kPa, and the temperature is kept for 60 minutes; when the temperature in the sintering furnace rises to 1420°C, the high-purity argon loading in the sintering furnace is increased to increase the pressure in the sintering furnace to 5.6MPa; the pressure in the sintering furnace is maintained at 5.6MPa, and the temperature is continued to rise to 1440°C, and the temperature is kept for 15 minutes; the pressure in the sintering furnace is continued to be maintained at 5.6MPa, and the temperature is reduced to 1420°C at a rate of 15°C / min, and the temperature is kept for 100 minutes; the furnace temperature is reduced to 1000°C within 8 minutes; and the furnace is cooled to a product discharge temperature of less than 70°C;

[0040] F. Low temperature tempering: Tempering is carried out in a vacuum furnace at a tempering temperature of 400°C for 7 hours.

[0041] According to GB / T 3488.4-2022 "Metallographic determination of cemented carbide microstructure Part 4: Metallographic determination of porosity, uncombined carbon defects and decarburized phases", the microstructure inspection was carried out. The results showed that the alloy porosity was <A02, B00, which was a fully densified state, and there was no decarburized phase or carburized phase in the alloy. The microstructure of the alloy after corrosion by standard metallographic reagents was observed under a scanning electron microscope. The results showed that the alloy had a two-phase homogeneous structure of WC hard phase and Ni-based solid solution bonding phase, see Figure 1. According to GB / T 3488.2-2018 "Metallographic determination of cemented carbide microstructure Part 2: Measurement of WC grain size", the electron microscope photos were measured by the average intercept method. The results show that the WC hard phase in the alloy is composed of irregular grains with an average grain size of 0.3μm and dispersed small plate-like grains, among which the average length of the long strip WC grains is 1.6μm and the average width is 0.3μm. The transmission electron microscopy observation and analysis results show that there is a uniformly distributed nano-dispersed phase containing W, Cr, and V in the alloy bonding phase.

[0042] Example 2

[0043] The experimental raw materials are as follows: specific surface area is 3.47g / cm 3 , unsaturated carbon WC powder with an average particle size of 110nm and a total carbon content of 6.11%, carbonyl Ni powder with a Fisher particle size of 1.1μm, Cr3C2 powder with a Fisher particle size of 0.8μm, and VC powder with a Fisher particle size of 1.0μm. The preparation process is as follows:

[0044] A. Batching and dry premixing: The above raw material powders are used for batching so that the mass fraction of Ni in the raw material powder is 6%, the mass ratio of Cr3C2 to Ni is 18%, and the mass ratio of VC to Ni is 3.5%; the prepared raw material powders are poured into a dry mixing device, filled with Ar gas, and dry premixed for 1 hour under an Ar gas protective atmosphere to form a premix;

[0045] B. Wet grinding: using a drum ball mill and WC-8Ni-based cemented carbide grinding balls with an average grain size of 0.7 μm, the mass ratio of grinding balls to premix is ​​6:1, the grinding balls, the premix obtained in step A, a composite forming agent consisting of polyethylene glycol, paraffin and stearic acid accounting for 2.4% of the total mass of the mixture, and a mixed wet grinding medium of alcohol and hexane are added into a ball mill barrel, and the wet grinding time is 60 hours; wherein the mass proportions of polyethylene glycol, paraffin and stearic acid in the composite forming agent are 25%, 60% and 15% respectively, and the volume proportion of hexane in the wet grinding medium mixed solution is 8%;

[0046] C. Drying and granulating the mixture: preparing the wet-milled mixture into a mixture with an average particle size of less than 150 μm by vacuum drying and mechanical granulation;

[0047] D. Forming: According to the shape and size of the product, the granulated mixture is pressed into shape by molding process;

[0048] E. Removal and sintering of forming agent: The removal and sintering of forming agent are carried out in a 10MPa pressure sintering furnace, and the forming agent is removed according to the conventional forming agent removal process; after the removal of the forming agent, vacuum sintering is carried out in the furnace. When the temperature of the sintering furnace rises to 1300°C, high-purity argon is introduced to make the pressure in the sintering furnace reach 8kPa, and the temperature is kept for 80 minutes; when the temperature in the sintering furnace rises to 1430°C, the amount of high-purity argon loaded in the sintering furnace is increased to raise the pressure in the sintering furnace to 8MPa; the pressure in the sintering furnace is maintained at 8MPa, and the temperature is continued to rise to 1450°C, and the temperature is kept for 20 minutes; the pressure in the sintering furnace is continued to be maintained at 8MPa, and the temperature is reduced to 1430°C at a rate of 20°C / min, and the temperature is kept for 120 minutes; the furnace temperature is reduced to 1100°C within 10 minutes; and the product is cooled to a temperature of less than 70°C when the furnace is cooled;

[0049] F. Low temperature tempering: Tempering is carried out in a high-purity argon atmosphere, and the tempering temperature is kept at 450°C for 5 hours.

[0050] According to the relevant standards described in Example 1, the results show that the porosity of the alloy is <A02, B00, which is a fully densified state, and there is no decarburized phase and carburized phase in the alloy. The microstructure of the alloy after corrosion by standard metallographic reagents was observed under a scanning electron microscope. The results show that the alloy has a two-phase homogeneous structure of WC hard phase and Ni-based solid solution bonding phase. The WC hard phase is composed of irregular grains with an average grain size of 0.3μm and dispersed fine plate-like grains, among which the average length of the long strip WC grains is 1.7μm and the average width is 0.4μm. The transmission electron microscope observation and analysis results show that there is a nano-dispersed phase containing W, Cr, and V in a uniformly distributed state in the alloy bonding phase.

[0051] Example 3

[0052] The experimental raw materials are as follows: specific surface area is 3.90g / cm 3 , unsaturated carbon WC powder with a specific surface area average particle size of 98nm and a total carbon content of 6.05%, carbonyl Ni powder with a Fisher particle size of 1.1μm, Cr3C2 powder with a Fisher particle size of 0.8μm, and VC powder with a Fisher particle size of 1.0μm. The preparation process is as follows:

[0053] A. Batching and dry premixing: The above raw material powders are used for batching, so that the mass fraction of Ni in the raw material powder is 13%, the mass ratio of Cr3C2 to Ni is 25%, and the mass ratio of VC to Ni is 3%; the prepared raw material powders are poured into a dry mixing device, filled with Ar gas, and dry premixed for 2 hours under an Ar gas protective atmosphere to form a premix;

[0054] B. Wet grinding: using a drum-type ball mill and WC-8Ni-based cemented carbide grinding balls with an average grain size of 0.7 μm, the mass ratio of grinding balls to premix is ​​5:1, the grinding balls, the premix obtained in step A, a composite forming agent consisting of polyethylene glycol, paraffin and stearic acid accounting for 2.2% of the total mass of the mixture, and a mixed wet grinding medium of alcohol and hexane are added into a ball mill barrel, and the wet grinding time is 68 hours; wherein the mass proportions of polyethylene glycol, paraffin and stearic acid in the composite forming agent are 30%, 60% and 10% respectively, and the volume proportion of hexane in the wet grinding medium mixed solution is 10%;

[0055] C. Drying and granulating the mixture: preparing the wet-milled mixture into a mixture with an average particle size of less than 150 μm by vacuum drying and mechanical granulation;

[0056] D. Forming: According to the shape and size of the product, the granulated mixture is pressed into shape by molding process;

[0057] E. Removal and sintering of forming agent: The removal and sintering of forming agent are carried out in a 6MPa pressure sintering furnace, and the forming agent is removed according to the conventional forming agent removal process; after the removal of the forming agent, vacuum sintering is carried out in the furnace. When the temperature of the sintering furnace rises to 1250°C, high-purity argon is introduced to make the pressure in the sintering furnace reach 10kPa, and the temperature is kept for 70 minutes; when the temperature in the sintering furnace rises to 1410°C, the amount of high-purity argon loaded in the sintering furnace is increased to raise the pressure in the sintering furnace to 5MPa; the pressure in the sintering furnace is maintained at 5MPa, and the temperature is continued to rise to 1430°C, and the temperature is kept for 20 minutes; the pressure in the sintering furnace is continued to be maintained at 5MPa, and the temperature is reduced to 1410°C at a rate of 20°C / min, and the temperature is kept for 80 minutes; the furnace temperature is reduced to 1000°C within 5 minutes; and the product is cooled to a temperature of less than 70°C when the furnace is cooled;

[0058] F. Low temperature tempering: Tempering is carried out in a high-purity nitrogen atmosphere, and the tempering temperature is kept at 400°C for 8 hours.

[0059] According to the relevant standards described in Example 1, the results show that the porosity of the alloy is <A02, B00, which is a fully densified state, and there is no decarburized phase and carburized phase in the alloy. The microstructure of the alloy after corrosion by standard metallographic reagents was observed under a scanning electron microscope. The results show that the alloy has a two-phase homogeneous structure of WC hard phase and Ni-based solid solution bonding phase. The WC hard phase is composed of irregular grains with an average grain size of 0.3μm and dispersed fine plate-like grains, among which the average length of the long strip WC grains is 1.7μm and the average width is 0.4μm. The transmission electron microscope observation and analysis results show that there is a nano-dispersed phase containing W, Cr, and V in a uniformly distributed state in the alloy bonding phase.

[0060] Comparative Example 1

[0061] The experimental raw materials and alloy composition ratios were the same as those in Example 1; except that dry premixing was not used, the direct wet grinding time of the mixed material was 50 hours, and low-temperature tempering was not used, the other preparation process parameters were the same as those in Example 1. The metallographic observation and analysis test results showed that there were obvious bonding phase aggregation and coarse WC grain agglomeration defects in the alloy, and the WC grain inclusion was relatively coarse, as shown in FIG. Figure 2 The microstructure of the alloy after being corroded by standard metallographic reagents was observed under a scanning electron microscope. The results showed that there were very few WC grains with obvious plate-like crystal characteristics in the alloy. The transmission electron microscope observation and analysis results showed that no nano-dispersed phase was observed in the alloy bonding phase.

[0062] Comparative Example 2

[0063] The WC raw material used in the experiment has a specific surface area of ​​3.86 g / cm 3 , saturated carbon WC powder with an average particle size of 99nm and a total carbon content of 6.14%, and the other raw materials are the same as in Examples 1 to 3. The alloy composition ratio is: the mass fraction of Ni in the raw material powder is 6%, the mass ratio of Cr3C2 to Ni is 12%, and the mass ratio of VC to Ni is 4%; the preparation process parameters of the alloy are the same as in Example 2. The results of scanning electron microscopy observation and analysis show that the alloy has a two-phase homogeneous structure of WC hard phase and Ni-based solid solution bonding phase. The average grain size of the WC hard phase in the alloy is 0.3μm, and WC grains with obvious plate-like crystal characteristics are rarely seen. Figure 3 .

[0064] Comparative Example 3

[0065] The experimental raw materials and alloy composition ratios are the same as those in Example 3; except that the sintering is not subjected to rapid cooling, but directly cooled from the sintering temperature with the furnace, the other preparation process parameters are the same as those in Example 3. The results of scanning electron microscopy and energy spectrum analysis show that the WC hard phase in the alloy is composed of ultrafine and nano grains with irregular morphology and dispersed small plate-like grains; in addition to the WC hard phase and Ni-based solid solution bonding phase, part of Cr3C2 is found in the alloy as an independent third phase, as shown in FIG. Figure 4 The arrow in the middle indicates the location. Transmission electron microscopy observation and analysis results show that no nano-dispersed phase is observed in the alloy bonding phase.

[0066] Comparative Example 4

[0067] Except that the mass ratio of Cr3C2 to Ni is 10.0%, the experimental raw materials, the content of Ni in the alloy, the mass ratio of VC to Ni and the alloy preparation process are the same as those in Example 3. The transmission electron microscopy observation and analysis results show that no nano-dispersed phase is observed in the alloy bonding phase.

[0068] Comparative Example 5

[0069] The ratio of raw materials and alloy components used in the experiment is the same as that in Example 3; except for the use of a single alcohol medium and a single polyethylene glycol forming agent accounting for 2.2% of the total mass of the mixture, the other preparation process parameters are the same as those in Example 3. The molded green compact was tested and found to have delamination and cracking defects. The green compact with the above defects was sintered in the same furnace as the green compact in Example 3, and obvious large cracks were still observed under the metallographic microscope, as shown in FIG. Figure 5 .

[0070] GB / T 3851-2015 "Determination Method of Transverse Fracture Strength of Cemented Carbide" (selecting Type B specimen), GB / T7997-2014 "Test Method for Vickers Hardness of Cemented Carbide" (selecting 30 kg load) and GB / T 33819-2017 "Babbitt Toughness Test for Cemented Carbide" were used to measure the bending strength (TRS), Vickers hardness (HV30) and Palmqvist fracture toughness (K Ic ), the test results are shown in Table 1.

[0071] Table 1 Alloy performance test results in Examples and Comparative Examples

[0072]

Claims

1. A twin-crystal and dispersion-strengthened WC-Ni based cemented carbide, characterized in that: The alloy is composed of a hard phase component WC, a bonding metal Ni and a composite grain growth inhibitor; the composite grain growth inhibitor is Cr3C2 and VC; the mass fraction of the bonding metal Ni in the alloy is 6.0-13.0%; the mass ratio of the grain growth inhibitor Cr3C2 to Ni is 12.0-25.0%, the mass ratio of VC to Ni is 3.0-4.0%, and the total amount of the composite grain growth inhibitor added exceeds its solid solution amount in the bonding phase under room temperature; the W The WC hard phase in the C-Ni based cemented carbide is composed of irregular grains with an average grain size of less than 0.5 μm and dispersed fine plate-like grains. The typical morphological feature of the fine plate-like WC grains in the polished cross section of the alloy is long strips with an average length of less than 2.2 μm and an average width of less than 0.5 μm. The bonding phase is a Ni-based solid solution formed by the solid solution of alloy components W, Cr, V and C in the bonding metal Ni during the alloy sintering process, and a nano-dispersed phase exists in the Ni-based solid solution.

2. A method for preparing twinned and dispersion strengthened WC-Ni based cemented carbide, characterized in that: The raw materials used include: nano-scale unsaturated carbon WC powder with an average particle size of less than 120nm in specific surface area, carbonyl Ni powder with a Fisher particle size of less than 1.2μm, and Cr3C2 powder and VC powder with a Fisher particle size of less than 1.2μm; the total carbon content of the unsaturated carbon WC powder is less than 6.12%; the preparation process includes: A. Batching and dry premixing: nanometer-scale unsaturated carbon WC powder having a total carbon content of less than 6.12% and an average particle size of specific surface area less than 120nm, carbonyl Ni powder having a Fisher particle size of less than 1.2μm, and Cr3C2 powder and VC powder having a Fisher particle size of less than 1.2μm are batched so that the mass fraction of Ni in the raw material powder is 6.0-13.0%, the mass ratio of Cr3C2 to Ni is 12.0-25.0%, and the mass ratio of VC to Ni is 3.0-4.0%; the prepared raw material powders are dry premixed for 1-2 hours in an Ar gas protective atmosphere to form a premix; B. Wet grinding: Wet grinding the WC-Ni based cemented carbide grinding balls, premix and composite forming agent in a wet grinding medium for at least 60 hours, wherein the mass ratio of cemented carbide grinding balls to premix is ​​4:1 to 6:1, and the amount of the composite forming agent added is 2.2 to 2.4% of the total mass fraction of the powder; C. Drying and granulating the mixture: using spray drying granulation or vacuum drying and mechanical granulation technology to prepare the wet-milled mixture into a mixture with an average particle size of less than 150 μm; D. Forming: Press the granulated mixture into shape according to the shape and size of the product; E. Removal of forming agent and sintering: a. Remove the forming agent from the green compact; b. After the forming agent is removed, vacuum sintering is performed in a pressure sintering furnace. When the temperature of the sintering furnace rises to 1250-1300°C, high-purity argon is introduced to make the pressure in the sintering furnace reach 8-10 kPa, and the temperature is kept for 60-80 minutes; c. When the temperature in the sintering furnace rises to 1410-1430°C, the amount of high-purity argon loaded in the sintering furnace is increased to raise the pressure in the sintering furnace to 5-8 MPa. a; d. Maintain the pressure in the sintering furnace at 5-8MPa, continue to raise the temperature to 1430-1450℃, and keep it warm for 15-20 minutes; e. Continue to maintain the pressure in the sintering furnace at 5-8MPa, reduce the temperature to 1410-1430℃ at a rate of 10-20℃ / min, and keep it warm for 80-120 minutes; f. Reduce the furnace temperature to 1000-1100℃ within 5-10 minutes; g. Cool down with the furnace to a product outlet temperature of less than 70℃; F. Low temperature tempering: The tempering temperature is 400-450℃, the tempering time is 5-8 hours, and it is carried out under a protective atmosphere.

3. The method for preparing twinned and dispersion strengthened WC-Ni based cemented carbide according to claim 2, characterized in that: The wet grinding in step B is carried out in a drum ball mill.

4. The method for preparing twinned and dispersion strengthened WC-Ni based cemented carbide according to claim 2, characterized in that: The average grain size of the WC hard phase in the WC-Ni based cemented carbide grinding ball is less than 0.8 μm, and Ni is used as a single bonding metal.

5. The method for preparing twinned and dispersion strengthened WC-Ni based cemented carbide according to claim 2, characterized in that: The wet grinding medium in step B is a mixed solution of alcohol and hexane; wherein the volume proportion of hexane in the wet grinding medium mixed solution is 5-10%.

6. The method for preparing twinned and dispersion strengthened WC-Ni based cemented carbide according to claim 2, characterized in that: The composite forming agent in step B is composed of polyethylene glycol, paraffin and stearic acid, wherein the mass proportions of polyethylene glycol, paraffin and stearic acid in the composite forming agent are 20-30%, 60-70% and 10-15% respectively, and the total amount of the three is 100%.

7. The method for preparing twinned and dispersion strengthened WC-Ni based cemented carbide according to claim 2, characterized in that: The protective atmosphere in step F is vacuum or high-purity argon or high-purity nitrogen inert gas.

Citation Information

Patent Citations

  • Novel WC-based hard alloy material and preparation method thereof

    CN101892411A

  • Ultrafine / nanocrystalline carbide alloy binding phase and preparation and application thereof

    CN103276270A

  • Preparation method of chromium-vanadium-tungsten compound carbide strengthened and toughened WC-Ni hard alloy

    CN114574727A

  • Superfine particle hard alloy as well as preparation method and application thereof

    CN116121615A

  • High-strength corrosion-resistant ultra-fine grain WC-Ni-based hard alloy and preparation method thereof

    CN118497583A